Ventilasi Noninvasif pada Obstructive Sleep Apnea dan Obesity Hypoventilation Syndrome - Herikurniawan, Herikurniawan; Audrey, Joanna; Adelya, Firina (Jurnal Penyakit Dalam Indonesia, 2024)
Chronic respiratory disease such as obstructive sleep apnea (OSA) and obesity-hypoventilation syndrome (OHS) remain are respiratory sleeping disorder that gradually affect quality of life. Comprehensive treatment such as the use of non-invasive ventilation (NIV) is a method adopted to improve the patient’s quality of life. The correct choice of NIV mode, mask and titration methods will provide optimal therapeutic effects to the patient. This article review lays out an update on the use of non-invasive ventilation as the treatment of OSA and OHS.